2016
DOI: 10.1515/njmr-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Origin and Destination Country Skills for Labour Market Attachment of Immigrants from Pakistan, Iran and Turkey

Abstract: This study explores how qualifications acquired prior to migration affect employment of adult immigrants in the destination country. It explores the direct effect as well as indirect effects arising through destination country investments. The study combines survey information on destination country language proficiency and education level from the country of origin with administrative records on employment and education acquired in the destination country. The results neither show evidence of direct transfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Unfortunately, the register data does not allow us to separate between education acquired in the country of origin and that acquired after arriving in Sweden. This is unfortunate considering that the latter may be relevant for immigrants' employment prospects (Arendt et al 2020). To get more correct measures of both establishment and level of education, we also control for current participation in education.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the register data does not allow us to separate between education acquired in the country of origin and that acquired after arriving in Sweden. This is unfortunate considering that the latter may be relevant for immigrants' employment prospects (Arendt et al 2020). To get more correct measures of both establishment and level of education, we also control for current participation in education.…”
Section: Methodsmentioning
confidence: 99%
“…General ALMPs comprise four types of interventions-following classifications from OECD (OECD, 2004) and Eurostat (Eurostat 2005) (Arendt & Pozzoli, 2013, Arendt, Pohl Nielsen, & Jakobsen, 2016. Therefore, we will divide the training programmes into two subgroups: (1a) classroom training and (1b) on-the-training/work experience.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Training is a classical type of ALMP. Previous studies have shown that it is important to distinguish between classroom‐training and on‐the‐job training (Arendt & Pozzoli, 2013, Arendt, Pohl Nielsen, & Jakobsen, 2016). Therefore, we will divide the training programmes into two subgroups: (1a) classroom training and (1b) on‐the‐training/work experience. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the authorities and professional bodies scrutinise the skill content and skill level of a foreigntrained professional, employers and clients are relieved from this task. Employers may be hesitant to hire immigrants if they doubt the academic content of foreign credentials or immigrants' language proficiency and cultural competence more generally (Arendt, Nielsen & Jakobsen 2017;. However, the licensing authority performs an evaluation of the skills and suitability of the practitioner, which can increase the trustworthiness of the practitioner.…”
Section: Licensure and The Consequences For Skilled Migrantsmentioning
confidence: 99%